Pemanfaatan Teknologi Pencetak Getuk Pisang Otomatis dan Pelatihan Manajemen Wirausaha untuk Meningkatkan Omset Pelaku Usaha Getuk Pisang Raja Nangka Kediri - Arif, Saiful; Aalin, Elmi Rakhma; Jainudin, Muhamad (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
In running his business, Mr Suryono still has many shortcomings which become obstacles especially in the equipment used. Production process equipment still uses manual tools and uses hands. This condition will affect the quality and uniformity of banana getuk. Another problem experienced by partners is the lack of managerial understanding which includes production, capital, financial administration, marketing and promotion which is still not a major concern but is an issue that will implicitly affect the calculation of business profits. To overcome these problems, the PKM implementation team provided a solution to the problem in the form of machine operation and maintenance training and business management training. After this implementation, the implementation team has reached the desired initial target of 53% increase in PKM partner turnover. In addition to these targets, the implementation team has also produced other outcomes in the form of proceedings from two national seminars, publication in print / electronic mass media, enhancing the competitiveness and application of science and technology, as well as TTG innovations in the form of automatic banana getter printing machines and sawdust fuel stoves. wood.